Efficient Implementation of 2D Barcode Verification Algorithm for IoT Applications - Al-Ghaili A.M.; Abdul Rahim F.; Azman F.; Kasim H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bar codes; Big data; Cryptography; Network security; 2-D barcodes; Efficient implementation; Internet of Things (IOT); Security Architecture; Security objectives; Smart access; Two-dimensional barcode; Verification algorithms; Internet of things